2017
DOI: 10.1155/2017/2048591
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Evaluation of Rock Dynamic Test with Split-Hopkinson Pressure Bar

Abstract: Feasibility of rock dynamic properties by split-Hopkinson pressure bar (SHPB) was experimentally and numerically evaluated with ANSYS/LS-DYNA. The effects of different diameters, different loading rates, and different propagation distances on wave dispersion of input bars in SHPB with rectangle and half-sine wave loadings were analyzed. The results show that the dispersion effect on the diameter of input bar, loading rate, and propagation distance under half-sine waveform loading is ignorable compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Disc Specimens. The stress balance factor, the dimensionless stress difference at both ends of the specimen, has been defined and widely used [29,33,[45][46][47]. It quantifies the stress balance of the specimen during dynamic impact.…”
Section: Calculation Methods Of Dynamic Stress Balance Factor Ofmentioning
confidence: 99%
“…Disc Specimens. The stress balance factor, the dimensionless stress difference at both ends of the specimen, has been defined and widely used [29,33,[45][46][47]. It quantifies the stress balance of the specimen during dynamic impact.…”
Section: Calculation Methods Of Dynamic Stress Balance Factor Ofmentioning
confidence: 99%
“…An observed signal at that point will indicate there is probably some reflection from the bearings supporting the bars. However Kang et al (2017) found that this problem is difficult to isolate and quantify as there may be other sources of waves. Alignment of the mounting brackets is performed by pointing a laser down the center of the launch tube.…”
Section: Issn: 2456-0766 Wwwijlremorg || Volume 08 -Issue 03 || May-j...mentioning
confidence: 99%
“…The constant strain rate is mainly dependent on the rise of the incident pulse which can induce premature failure long before dynamic stress equilibrium could ever be reached in the sample. As a rule of thumb, the loading stress wave needs approximately 3 to 4 rounds to travel within the specimen for the stress to achieve an equilibrium (Kang et al, 2017). For the split Hopkinson bar to obtain accurate measurements, the dynamic loading must be slow enough so that the specimen is experiencing an essentially quasi-static load.…”
Section: Placement Of Strain Gagesmentioning
confidence: 99%
“…Mahanta et al studied the effects of strain rate on fracture toughness and energy release rate of gas shales [33]. Peng used the split-Hopkinson pressure bar to conduct the Brazilian disc test and concluded that the time required to achieve a uniform stress state in specimen for the half-sine incident pulse is noticeably shorter than that for the perfectly rectangular incident pulse [37]. us, the influence of temperature on rock mechanical properties has been widely studied worldwide.…”
Section: Rock Mechanism Under Dynamic Loadsmentioning
confidence: 99%